KEBIJAKAN PEMERINTAH INDONESIA POST COVID-19 DALAM PERSPEKTIF GOOD GOVERNANCE - Subagyo, Ian; Dewi, Dian Suluh Kusuma (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Covid-19 was first discovered in Indonesia in early 2020, this pandemic has been going on for more or less 2 years. The current outbreak of the Corona virus or Covid-19 can be controlled properly. Even with high community mobility, Covid-19 cases can be suppressed well. The purpose of this study is to find out the policies of the post-Covid-19 government from the perspective of good governance. The results of this study are several post-Covid-19 policies made by the Indonesian government, including the non-applicability of quarantine obligations for foreign travelers (PPLN). covering the areas of Batam, Bintan and Bali and then expanding this policy to all corners of the country, no longer imposing the obligation to carry out Covid-19 tests including PCR and Rapid tests, reopening face-to-face schools with strict health protocols, allowing tarawih prayers and Eid prayers in congregation in mosques or open fields, allowing going home on condition that they must third vaccine or booster, reopening the Hajj 1443 H/2022 and easing the use of masks where people are allowed to remove masks in open spaces. This study uses descriptive qualitative research methods with data collection techniques for literature study by collecting data from online media and official government websites, scientific journals and also articles related to related research. In order to facilitate the analysis of large amounts of research data, during data processing the Nvivo 12 Plus application is used to analyze the data and ensure the correctness of the data.Keywords : Policy, Covid-19, Post Covid-19, Good Governance